PIDANA MATI : HUKUM POSITIF DAN HUKUM ISLAM - Qori Rizqiah H Kalingga (JURNAL JUSTIQA, 2019)
One of the most severe forms of sanctions in criminal law is the death penalty. The death penalty issue has been debated for hundreds of years by experts in criminal law and criminology until now. Debate the pros and cons of the death penalty, it's a debate that will never end until whenever. Many of the cons, but not a few who expressed kesetujuannya. The group agreed reasoned, if consciously convicted criminal action and show a grave violation of the right to life each other then the state is not obligated to protect and respect the right to life of the convicted person. The perpetrators of serious crimes should face the death penalty so that it becomes a deterrent effect. While rejecting the death penalty argue that this one sentence is a dark shadow in the application of human rights, namely the right to life form. Moreover, many people who consider the death penalty in Islam is very cruel and only an impingement "revenge" only. For a more clear and compelling of these problems the author tried to describe some of the issues related to capital punishment, namely what is the difference between the death penalty in the positive law of Indonesia and the Islamic criminal law and how the death penalty in the view of Islamic law.